The Southern Books Competition at Twenty-five: A Silver Anniversary Tribute - Marshall, John David (The Plate Shop, Inc. Birmingham, Alabama, 1980)
The Southern Books Competition at Twenty-five: A Silver Anniversary Tribute. Compiled by John David Marshall. The Southeastern Library Association. Copyright 1980 by Howick House Type by The Plate Shop, Inc. Birmingham, Alabama.
The Southern Books Competition at Twenty-five: A Silver Anniversary Tribute. 1 digitized book. PDF. 224 pages. 392 MB (411,541,294 bytes).
Keywords: Books; Southeastern Library Association